Economic Status of Agricultural Labourers in Thiruvananthapuram District - Unnikrishnan G (Department of Agricultural Economics, College of Agriculture, 1994)
The study ‘Economic status of agricultural labourers in Thiruvananthapuram district’ was carried out with the following objectives. 1. To understand the levels of employment, under employment and unemployment of the agricultural labourers of Thiruvananthapuram district. 2. To study the wages rates and modes of payment of the wages. 3. To estimate the income levels of the ALHH. 4. To assess the expenditure pattern of the ALHH. 5. To estimate the extent of poverty , if any 6. To estimate the levels of indebtedness and savings. 7. To assess the support through the various welfare programmes for the selected households. 8. To understand details such as social participation, cosmopoliteness, aspiration levels etc. 9. To study the levels of political participation of the ALHH The study was conducted in the Neyyatinkara subdivision of the district in 4 randomly selected krishibhavans. Sample size of the study was 120 and equal number of respondents were selected from each of the 4 Krishibhavans. Personal interviews were conducted to collect the data from the respondents with the help of a pre-tested and well structured questionnaire. The variables used in the study included basic family particulars, education level of the respondent, level of employment and details of wages, land holding size and land holding pattern, possession of farm implements, consumer durables, livestock status, value of permanent assets, dependence on the PDS, income and expenditure pattern of the households, benefits from welfare programmes, indebtedness and savings levels of the households, social participation and other relevant characteristics which are useful in measuring the economic status of a household. For measuring the variables suitable scales were used which were used by earlier researchers with modifications wherever needed and in some cases suitable scales and classes were formed. Data collected was coded, tabulated and analysed with suitable statistical tools. Some of the important findings of this study are 1. Majority of the house holds were thatched ones and family compositions mainly nuclear. 2. The average family size was four and large proportion of the labourers belonged to the age group 35-55. 3. About 67 per cent of the labourers were moderately under employed and 23 percent severly underemployed. 4. Wage rates of both male and female labourers were above the minimum wage rates fixed by the government and was mainly paid in cash only. 5. Disparity was seen in wages for male and female labourers, the latter earning only about 70 per cent of the former, per day even though working hours were same for both. 6. Average annual income per household was about Rs 29887 and percapita income was about Rs 8078. 7. Eighty nine percent of the ALHH depended wholly or partially on the PDS to fulfill their food requirements. 8. Cereals had the highest share in food expenses for majority of households and food expenses formed the major share in total expenses 9. Expenditure was significantly and directly related with income. 10. It was observed that 18 percent of the ALHH were below and 21 percent marginally above the poverty line based on consumption expenditure. 11. Anti-poverty programmes were yet to reach one third of the population and even the benefited households got only a meager amount per household. 12. Dependence for credit by the ALHH was equal on both formal and non-formal agencies and 84 percent of them had availed credit. 13. Sixty five percent of the households that availed credit had amounts overdue against them. 14. Financial base of the households was unstable at all levels of income. 15. Family size and number of days of employment was inversely and significantly related to credit amount overdue. 16. About half of the total households had no savings and the others mainly invested in non-formal agencies only. 17. Social participation level was low for most of the ALHH. 18. Most of the ALHH were highly exposed to mass media, had high levels of health and hygiene, cosmopoliteness and aspirations. 19. Majority of the respondents were members of registered political parties and had high political awareness. The results obtained from the study was similar to those obtained in earlier studies with regard to most of the variables. The agricultural labourers were still poor and down-trodden and their upliftment needs greater attention than that given now. By proper policy modifications and implementation it can be made sure that their upliftment is not a herculian task.